Sublobar Resection for Clinical Stage IA Non-small Cell Lung Cancer in the United States - Speicher, Paul J (Clin Lung Cancer, 2015)
This study evaluated the use of lobectomy and sublobar resection for clinical stage IA non-small cell lung cancer (NSCLC) in the National Cancer Data Base. A total of 39,403 patients were included for analysis, of whom 9,667 (24.5%) underwent sublobar resection. Lobectomy was associated with superior survival, however among sublobar resection patients, lymph node sampling was associated with improved outcomes although was performed in a minority of sublobar patients. This study emphasizes the need for nodal sampling when performing sublobar resection even for the earliest stages of NSCLC. BACKGROUND: This study evaluated the use of lobectomy and sublobar resection for clinical stage IA non-small cell lung cancer (NSCLC) in the National Cancer Data Base (NCDB). METHODS: The National Cancer Data Base from 2003–2011 was analyzed to determine factors associated with the use of a sublobar resection versus a lobectomy for the treatment of clinical stage IA NSCLC. Overall survival was assessed using the Kaplan-Meier method and Cox proportional hazards modeling. RESULTS: Among 39,403 patients included for analysis, 29,736 (75.5%) received a lobectomy and 9,667 (24.5%) received a sublobar resection: 84.7% wedge resection (n=8192); 15.3% segmental resection (n=1475). Lymph node evaluation was not performed in 2,788 (28.8%) of sublobar resection patients, and 7,298 (75.5%) of sublobar resections were for tumors ≤2cm. Following multivariable logistic regression, older age, higher Charlson/Deyo comorbidity scores, smaller tumor size, and treatment at lower-volume institutions were associated with sublobar resection (all p<0.001). Overall, lobectomy was associated with significantly improved 5-year survival compared to sublobar resection (66.2% vs. 51.2%, p<0.001, adjusted hazard ratio 0.66, p<0.001). However among sublobar resection patients, nodal sampling was associated with significantly better 5-year survival (58.2% vs. 46.4%, p<0.001). CONCLUSIONS: Despite adjustment for patient and tumor related characteristics, a sublobar resection is associated with significantly reduced long-term survival as compared to a formal surgical lobectomy among patients with NSCLC, even for stage 1A tumors. For patients who cannot tolerate lobectomy and are treated with sublobar resection, lymph node evaluation is essential to help guide further treatment.